Peningkatan Hasil Pembelajaran Sejarah Indonesia Dengan Metode Sambung Rasa - Latar, Jumila (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2022)
History education in Senior High School allows teachers to develop learning concepts or programs that train and equip students with the necessary skills, critical thinking abilities, and effective collaboration skills. It also aims to provide students with broad reasoning abilities, foster moral values, beliefs, and justice, as well as enhance their affective experiences and abilities. Socially, it helps build resilience, self-esteem, and a sense of responsibility. The method used in this research is Classroom Action Research (CAR). The results of the study indicate that (1) the Sambung Rasa method can help enhance teacher activity in the teaching and learning process; (2) the Sambung Rasa method can improve the teacher's ability to create a conducive learning environment; (3) teachers can maintain consistency between learning objectives and the topics taught; and (4) in terms of student learning satisfaction, the Sambung Rasa method can provide students with emotional involvement, learning experiences, and intellectual growth.